The Role Of Financial Reporting In Companies - Agustina, Ika (Journal of Management, 2024)
This study looks at how firms disclose their finances. Management may monitor a company's growth by participating in recording, accounting, and reporting. Thus, financial reporting based on a decision-making approach is an excellent instrument for measuring and monitoring a company's financial performance over time. Studying finance and other economic theories is vital for gaining a rapid comprehension of this concept. Accounting professionals must understand what "usability" is and how to enhance the usability of financial statements. Additionally, a clear explanation is essential. Decision-making and investment theory helps us comprehend the fundamentals of financial reporting information